Karakteristik dan Transformasi Pelayanan Bimbingan dan Konseling dalam Sistem Pendidikan di Era Merdeka Belajar - Intan Nurmaliya; Titin Sunarti; Fifi Hariyani; Niswah Ziyan Ahlia; Nurwahyuwana Nurwahyuwana (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The need for adaptive guidance and counseling services in response to changes in the educational paradigm in the Merdeka Belajar policy. Changes in student characteristics, the dynamics of educational policy, and demands for character building and independent learning place guidance and counseling services as a strategic element in the education system. This study aims to analyze the characteristics and transformation of guidance and counseling services in supporting the implementation of Merdeka Belajar. The research approach used is qualitative with a library research method through a critical review of relevant scientific journal articles and official national reports. The data were analyzed using content analysis techniques to identify patterns, themes, and trends in guidance and counseling service practices. The results of the study show that guidance and counseling services are characterized by a focus on student development, a preventive nature, and integration with the learning process. The transformation of services is marked by a paradigm shift towards flexible, collaborative services and the strengthening of the professionalism of counselors and teachers, so that guidance and counseling play an important role in realizing education that is student-centered in the era of Merdeka Belajar.